Eksistensi Tradisi Mertuq pada Masyarakat Sasak di Desa Wakan Kecamatan Jerowaru Kabupaten Lombok Timur - Sukron Azhari; Sukardiman (Jurnal Sosiologi Agama Indonesia (JSAI), 2021)
This article examines the mertuq tradition among the Sasak people, who are faced with sophisticated modern medical tools in treating diseases. This study uses a quantitative descriptive model. Data were obtained from in-depth interviews with several key informants selected using purposive techniques. The research was conducted in Wakan Village, Jerowaru District, East Lombok Regency. This study indicates that the existence of the mertuq treatment of the Sasak community cannot be separated from the belief and trust in carrying it out. The people of Wakan Village still maintain mertuq as traditional medicine in overcoming disease even though medical treatment has been so rapid. The people of Wakan Village believe in the magic and efficacy of Mertuq's therapy because it is part of their ancestral heritage.